NEGOCIOS Y POLÃTICA EN AMÉRICA LATINA: EL RIESGO POLÃTICO COMO FACTOR IMPONDERABLE PARA LOS INVERSIONISTAS - Nostti, Raúl Bringas (European Scientific Journal, ESJ, 2013)
ï»¿ï»¿In recent years, international business analysts and rating agencies have developed a wide array of strategies in order to measure investment risks in different countries. Under the concept of â€œCountry Riskâ€, pundits believe they are able to foresee the possible problems investors will face when entering a specific market. The imperfect econometric particularities of â€œCountry Riskâ€ analysis have given life to â€œPolitical Riskâ€ studies, which pretend, with a sociopolitical stance, to solve the inherent problems of more technical approaches. However, in the case of Latin-American economies, both strategies are of little help, no matter what assurances analysts and rating agencies offer to the public. Latin-American countries are unpredictable. In just a few months, even the best ranked country may become, by unforeseeable circumstances, the ruin of investors. Due to its particular characteristics, Latin-America is prone to major changes in any direction. A strong populist discourse has broad sympathies among the population. Thanks to relatively robust democratic institutions, a change in economic direction is around the corner in every single Latin-American scenario, without the need of a revolution. In this region of the world, â€œCountry Riskâ€ and â€œPolitical Riskâ€ analysis are just a rhetorical illusion.